Farmers or foresters: the use of tree in the sylvopastoral systems of the Atlantic Zone of Costa Rica - Paap, P.F. (CATIE, Turrialba (Costa Rica). Atlantic Zone Programme Agricultural | University Wageningen, Wageningen (Países Bajos) | Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
78 páginas, 14 figuras, 12 tablas. También como: Field Report - Atlantic Zone Programme / CATIE-AUW-MAG; no. 98